AUDIT SISTEM INFORMASI FUNGSI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PADA CV. NR HERBALCARE, JOMBANG - Sugianto, Yosua Ngurah; Paramitha, Melvie (Universitas Widya Kartika Surabaya, 2024)
N203R implements a marketing information system to manage marketing. However, theinformation system has not been able to produce the required information. The purpose ofcarrying out an information system audit in the marketing function is to provide a report on theperformance assessment of the information system in the marketing function and providerecommendations for increasing the effectiveness and efficiency of parts of the informationsystem that are still lacking. The focus of this research is referring to the marketing functioninformation system audit at CV. NR Herbalcare, Jombang. The type of data used is descriptivequalitative data and the data source is primary data. The methods used in the research areobservation and interviews. In this research, researchers will carry out audit planning, carryout audit testing, as well as audit reporting and recommendations. The research results foundvarious findings in the marketing information system implemented by N203R that needed to beimproved. Meanwhile, suggestions and recommendations based on the findings are alsoincluded.